1999
DOI: 10.1111/j.1572-0241.1999.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Symptoms Identify Different Subgroups in Functional Dyspepsia

Abstract: Different subgroups exist among patients with functional dyspepsia seen in a referral center. They can be identified by the predominant symptom and are characterized by different demographic, clinical, and pathophysiological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 26 publications
5
58
0
Order By: Relevance
“…These observations have potential implications for the investigation and management of disordered gastric emptying in patients with diabetes. The observed relationship between abdominal bloating/fullness and gastric emptying in patients with diabetes is consistent with recent studies of patients with functional dyspepsia (11)(12)(13). The total score for gastric symptoms correlated weakly with solid emptying but not with liquid emptying.…”
Section: Determinants Of Gastric Emptyingsupporting
confidence: 78%
See 1 more Smart Citation
“…These observations have potential implications for the investigation and management of disordered gastric emptying in patients with diabetes. The observed relationship between abdominal bloating/fullness and gastric emptying in patients with diabetes is consistent with recent studies of patients with functional dyspepsia (11)(12)(13). The total score for gastric symptoms correlated weakly with solid emptying but not with liquid emptying.…”
Section: Determinants Of Gastric Emptyingsupporting
confidence: 78%
“…In most of these studies, symptoms have been evaluated using either a global symptom score and/or individual upper gastrointestinal symptoms classified as either "present" or "absent," without considering their severity (2-7). This approach may be relevant to the interpretation of these observations, particularly because recent studies of patients with dyspepsia of unknown origin have demonstrated a close association among specific symptoms, such as postprandial fullness with delayed gastric emptying, particularly when these symptoms are severe enough to influence usual activities (11)(12)(13). There is also evidence that gastric emptying in patients with functional dyspepsia may be influenced by demographic factors, such as sex and body weight (11).…”
mentioning
confidence: 99%
“…4 Studies have shown correlations between this subdivision and the presence of Helicobacter pylori infection or delayed gastric emptying, 16 and between this subdivision and response to acid-suppressive therapy. 17 However, the subdivision has also been criticized because of the significant overlap between the symptom subgroupings, the considerable number of patients who do not fit into one of the subgroups, and the lack of adequate value in predicting underlying organic disease.…”
Section: Subgroups Of Functional Dyspepsia Patientsmentioning
confidence: 99%
“…A delayed GE in patients suffering from FD was found with an incidence that varies from 15% to 50% of cases [13]; therefore it is a non-specific disease marker [14]. Inversely, according to observations of Stanghellini et al certain dysmotility symptoms and their severity were strong risk indicators fora delayed GE [15].…”
Section: Discussionmentioning
confidence: 99%